1992
DOI: 10.1007/bf00180447
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB3 gene alleles in Caucasian patients with Graves' disease

Abstract: Graves' disease (GD) is a human leukocyte antigen (HLA) linked organ-specific autoimmune disease. In German GD patients the disease is associated with HLA specificities of the HLA-DRw52 family (HLA-DR3, -DR5, and DR6; HLA-DRB3 positive HLA haplotypes). Recently, a strong association with a HLA-DRB3 restriction fragment length polymorphism gene has been described. To study HLA-DRB3 alleles and their association with the disease, a large cohort of controls (n = 3724) and GD patients (n = 304) was analyzed. HLA-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
1
28
2
1
Order By: Relevance
“…DRB3 is known to be associated with Graves' disease, as in our study here and as previously reported by others in patients with a variety of ages of disease onset (5,22). However, DRB1*03 and DRB3 are in such tight linkage disequilibrium (23) that it has been difficult to identify which is the primary locus.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…DRB3 is known to be associated with Graves' disease, as in our study here and as previously reported by others in patients with a variety of ages of disease onset (5,22). However, DRB1*03 and DRB3 are in such tight linkage disequilibrium (23) that it has been difficult to identify which is the primary locus.…”
Section: Discussioncontrasting
confidence: 39%
“…Human leukocyte antigens (HLA) DRB1*0301, DRB3*0101, DQA1*0501, and DQB1*0201 have been reported to be associated with Graves' disease in Caucasian patients (1,(5)(6)(7)(8). However, the primary locus (loci) has not been resolved, whereas HLA associations with Graves' disease have not been fully addressed in terms of age at onset.…”
Section: G Raves' Disease Is An Autoimmune Thyroid Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…As this extended haplotype has been consistently reported to be associated with GD in most, 7,9 but not all, 22,23 ethnic groups and because LD is strong across the HLA region it is important to exclude the HLA-DRB1*03 haplotype as the explanation for association with the TNF-a SNPs. Furthermore, the HLA-DRB1*03 haplotype is also associated with an increase in TNF-a production.…”
Section: Discussionmentioning
confidence: 99%
“…* 0501 in Graves' disease patients, as compared to controls (15)(16)(17). HLA haplotype DRB1 * 0304-DQB1 * 02-DQA1 * 0501 is associated with a maximal risk in autoimmune thyrotoxicosis (17).…”
Section: Discussionmentioning
confidence: 93%